Pengaruh Disiplin Kerja dan Komitmen Organisasional terhadap Kinerja Karyawan pada PT. Pelabuhan Indonesia (Persero) Regional 4 Bitung - hutasoit, helen meilinda; rumawas, wehelmina; tamengkel, lucky (JURNAL ADMINISTRASI BISNIS, 2026)
This study aims to analyze the influence of work discipline and organizational commitment on employee performance at PT. Pelabuhan Indonesia (Persero) Regional 4 Bitung. The study used a quantitative approach with an associative design on 53 respondents from a total of 113 employees. Data were collected through a Likert scale questionnaire and analyzed using the Structural Equation Modeling– Partial Least Squares (SEM-PLS) method with SmartPLS 4. The results showed that work discipline had a positive and significant effect on employee performance and organizational commitment, and organizational commitment had a positive and significant effect on employee performance. These findings confirm that improving work discipline can improve employee performance both directly and through strengthening organizational commitment. Therefore, companies are advised to strengthen the implementation of work discipline and develop organizational commitment to improve work quality and productivity.